Employing foreign caregivers: A qualitative study of the perspectives of older stroke survivors - Yen-Nung Lin; Yosika Septi Mauludina; Beth E. Fields; Tsan-Hon Liou; Yu Su; Han-Ting Tsai; Feng-Hang Chang (PLoS ONE, 2025)
Background Global populations are aging, and the numbers of stroke survivors is increasing. Consequently, the need for caregiver support has increased. Because of this and demographic and socioeconomic changes, foreign caregivers are increasingly in demand in many developed countries. Therefore, the perspectives of older adult care recipients regarding foreign caregivers warrants attention. This study explored the experiences of older stroke survivors receiving care from foreign caregivers in Taiwan, examining their expectations, needs, and challenges. Methods This study employed a descriptive qualitative approach, conducting in-depth interviews with 23 older stroke survivors (mean age, 73.4 years; women, 47.8%). Thematic analysis was applied to transcribed data, with reflective memos aiding in meaning derivation. Methodological rigor was ensured through member checking, triangulation, and auditing. Results Three major themes emerged: the motivations for hiring a foreign caregiver, expectations of stroke survivors toward foreign caregivers, and challenges related to employing foreign caregivers. Stroke survivors expected foreign caregivers to be obedient, embrace the local language and culture, and be proficient in caregiving and homemaking. Various challenges, including communication difficulties, cultural differences, skill gaps, and unfavorable attitudes and behaviors among caregivers, were noted. Conclusions Foreign caregivers are a major part of the long-term care workforce and play a crucial role in stroke rehabilitation in aging Asian societies. Older stroke survivors often hire foreign caregivers to alleviate caregiving burdens, and they typically expect foreign caregivers to conform to their needs. However, employing foreign caregivers can be frustrating and stressful. Government intervention and open dialogue is necessary to improve care quality and prevent recurring caregiving problems and conflicts.